PENGARUH LATIHAN DRIBBLE SLALOM TERHADAP KETERAMPILAN DRIBBLING KLUB SMA NEGERI 1 SABAK AUH KABUPATEN SIAK - Gunawan '; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of the research is ability of Drilling in Soccer team of SMA Negeri 1 Sabak Auh Kabupaten Siak still far from expectation, So when the player transfer the ball, they can across the enemies easily then win the match. it can be seen from try out and friendly match even more a big match and this is one of the factor why they loss. This research was done at Soccer team of SMA Negeri 1 Sabak Auh Kabupaten Siak. This research used Experiment design to see the effect of using “Dribble Slalom”. The purpose of the research was to see the effect of using Dribble Slalom toward the ability of Drilling in Soccer team at SMA Negeri 1 Sabak Auh Kabupaten Siak. The population of this research was soccer team player of SMA Negeri 1 Sabak Auh at Siak district totaling 16 people. Exercise in this study is dribble slalom. The sampling technique used the total sampling, which was all the population had become the sample. The technique of collecting data was gotten from pre-test and post-test. The instrument of the research was a Dribbling test. The data analyzed by using T-test. Based on the data analysis, it can be seen from Tcount was 6,44 and Ttable 1,753. it meant Tcount>Ttable with the significant a=0,05. In conclusion, there was a different significant from Dribble Slalom in Soccer team of SMA Negeri 1 Sabak Auh Kabupaten Siak.